Use of whole sunflower seeds and urea as supplements to crop-residue-based diets for goats - Warambwa, A.R.; Ndlovu, L. (1992)
The potential use of diets based on maize stover and groundnut hay with either urea or sunflower seed as a supplement was investigated using indigenous Small East African goats. Four female goats fitted with permanent rumen cannulae were randomly assigned to a 2*2 changeover design to determine dry-matter loss using the nylon-bag technique. The sun flower-supplemented diet (11.45 VS 4.64%) but had a lower dry-matter degradation (45.08 VS 56.02)%. In another trial, 33 female goats were balanced for weight and assigned to two groups and given one of the two diets for 16 weeks. Intake and live weight changes were not different between the two diets. Both diets were adequate to maintain weight.